Circ_CLASP2 Regulates High Glucose-Induced Dysfunction of Human Endothelial Cells Through Targeting miR-140-5p/FBXW7 Axis - Zhang, Qin; Long, Jing; Li, Nannan; Ma, Xuelian; Zheng, Lisheng (Frontiers in Pharmacology, 2021)
Hyperglycemia exposure results in the dysfunction of endothelial cells (ECs) and the development of diabetic complications. Circular RNAs (circRNAs) have been demonstrated to play critical roles in ECs dysfunction. The current study aimed to explore the role and mechanism of circRNA CLIP-associating protein 2 (circ_CLASP2, hsa_circ_0064772) on HG-induced dysfunction in human umbilical vein endothelial cells (HUVECs). The quantitative real-time polymerase chain reaction (qRT-PCR) was used to assess the levels of circ_CLASP2, miR-140-5p and F-box and WD repeat domain-containing 7 (FBXW7). The stability of circ_CLASP2 was identified by the actinomycin D and Ribonuclease (RNase) R assays. Cell colony formation, proliferation and apoptosis were measured by a standard colony formation assay, colorimetric 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay and flow cytometry, respectively. Western blot analysis was performed to determine the expression of related proteins. Targeted correlations among circ_CLASP2, miR-140-5p and FBXW7 were confirmed by dual-luciferase reporter assay. High glucose (HG) exposure down-regulated the expression of circ_CLASP2 in HUVECs. Circ_CLASP2 overexpression or miR-140-5p knockdown promoted proliferation and inhibited apoptosis of HUVECs under HG conditions. Circ_CLASP2 directly interacted with miR-140-5p via pairing to miR-140-5p. The regulation of circ_CLASP2 overexpression on HG-induced HUVEC dysfunction was mediated by miR-140-5p. Moreover, FBXW7 was a direct target of miR-140-5p, and miR-140-5p regulated HG-induced HUVEC dysfunction via FBXW7. Furthermore, circ_CLASP2 mediated FBXW7 expression through sponging miR-140-5p. Our current study suggested that the overexpression of circ_CLASP2 protected HUVEC from HG-induced dysfunction at least partly through the regulation of the miR-140-5p/FBXW7 axis, highlighting a novel therapeutic approach for the treatment of diabetic-associated vascular injury.